Efficacy of power assisted microdebrider in endoscopic adenoid resection - Bakshi, Tanishka; Kelkar, Prasad; Toshniwal, Saket (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Nasal obstruction, snoring, mouth breathing, ear ache is some of the most common problems encountered in pediatric otorhinolaryngological practice. The most common cause for the above symptoms is adenoid hypertrophy. Methods: Patients with age group of 4-16 years with symptoms of adenoid hypertrophy such as snoring, mouth breathing, ear ache and adenoid hypertrophy confirmed by Diagnostic Nasal Endoscopy and Radiological Investigations were included. Previous H/o surgery for adenoidectomy, bleeding disorders, cases with cleft palate or previous H/o cleft palate repair neuromuscular / craniofacial anomalies were excluded. Results: 3.10 mean grade was seen among study participants, with 39% of children having Grade 4 adenoids, 35% having Grade 3 adenoids, and 26% having Grade 2 adenoids. Snoring, nasal obstruction, and breathing scores all decreased statistically significantly. Conclusions: A microdebrider-assisted adenoidectomy has shown to provide full clearance with only a minor increase in haemorrhage and process time.